2008
DOI: 10.1073/pnas.0710685105
|View full text |Cite
|
Sign up to set email alerts
|

The Parkinson's disease protein α-synuclein disrupts cellular Rab homeostasis

Abstract: ␣-Synuclein (␣-syn), a protein of unknown function, is the most abundant protein in Lewy bodies, the histological hallmark of Parkinson's disease (PD). In yeast ␣-syn inhibits endoplasmic reticulum (ER)-to-Golgi (ER3 Golgi) vesicle trafficking, which is rescued by overexpression of a Rab GTPase that regulates ER3 Golgi trafficking. The homologous Rab1 rescues ␣-syn toxicity in dopaminergic neuronal models of PD. Here we investigate this conserved feature of ␣-syn pathobiology. In a cell-free system with purifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
492
1
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 476 publications
(536 citation statements)
references
References 32 publications
29
492
1
5
Order By: Relevance
“…Several Rab GTPases were suggested to interact aberrantly with αS in Dementia with Lewy bodies (Soper et al, 2008(Soper et al, , 2011Sung et al, 2001). In addition, Rab proteins colocalize with glial inclusions containing αS in multiple system atrophy (Dalfo and Ferrer, 2005;Nakamura et al, 2000), Rab GTPases were found in vesicle clusters induced by αS overexpression in yeast (Gitler et al, 2008), and overexpression of the Rab GTPases Rab1, Rab3a and Rab8a decreased αS-induced neurotoxicity (Cooper et al, 2006;Gitler et al, 2008). The Rab GTPase Rab8a, which showed the strongest rescue of αS-toxicity in the nematode PD model (Gitler et al, 2008), is associated with recycling endosomes and basolateral trafficking events from the trans-Golgi network to the plasma membrane (Henry and Sheff, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several Rab GTPases were suggested to interact aberrantly with αS in Dementia with Lewy bodies (Soper et al, 2008(Soper et al, , 2011Sung et al, 2001). In addition, Rab proteins colocalize with glial inclusions containing αS in multiple system atrophy (Dalfo and Ferrer, 2005;Nakamura et al, 2000), Rab GTPases were found in vesicle clusters induced by αS overexpression in yeast (Gitler et al, 2008), and overexpression of the Rab GTPases Rab1, Rab3a and Rab8a decreased αS-induced neurotoxicity (Cooper et al, 2006;Gitler et al, 2008). The Rab GTPase Rab8a, which showed the strongest rescue of αS-toxicity in the nematode PD model (Gitler et al, 2008), is associated with recycling endosomes and basolateral trafficking events from the trans-Golgi network to the plasma membrane (Henry and Sheff, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In cellular and animal models of PD, αS overexpression disrupts vesicle trafficking between the endoplasmic reticulum (ER) and Golgi and overexpression of Rab1 attenuated αS toxicity (Cooper et al, 2006). Furthermore, Rab homeostasis is generally disturbed by αS in yeast with overexpression of Rab8a, Rab1 and Rab3a being partially protective against αS-induced toxicity (Gitler et al, 2008). In particular, Rab8a -the Rab GTPase that is responsible for modulating post-Golgi vesicle trafficking -increased the number of αS-overexpressing Caenorhabditis elegans with wild-type neurons from 15% to 40%, the strongest rescue effect found so far in this PD model (Gitler et al, 2008).…”
mentioning
confidence: 99%
“…Furthermore, a-synuclein could this way influence the proximity of synaptic vesicles to voltage-gated calcium channels in the plasma membrane, which has been shown to regulate the mode of exo-and endocytosis by influencing the local calcium environment [23]. [17,24,25]. However, on the other side, there is strong evidence that a-synuclein is a positive modulator of SNAREcomplex assembly, as shown in mice with a knockout of the cysteine-string protein a (CSPa).…”
Section: A-synuclein In Synaptic Vesicle Exocytosismentioning
confidence: 99%
“…Intriguingly, overexpression of Rab proteins has been shown to rescue a-synuclein toxicity [24,25,71]. Rab proteins are key players in the endosomal sorting of vesicles, and they are therefore crucial for retrieving new functional synaptic vesicles.…”
Section: [ 4 5 5 _ T D $ D I F F ] A-synuclein -A Possible Role In Slmentioning
confidence: 99%
“…The combined use of multiple animal models supported the roles of these proteins in α-syn toxicity. Suppression of cytotoxicity was identified in Drosophila (Rab1), rat neuronal cell cultures (Rab1 and Rab8A), and in C. elegans (Rab1 and Rab8A), where we showed that elevated expression of these specific Rab GTPases rescues DA degeneration induced by human α-syn overexpression [24,25] (Fig. 3b).…”
Section: Usefulness Of C Elegans α-Synuclein Model For Analysis Of Nmentioning
confidence: 56%